Literacy and Awakening: The Awakening of 1804/1805 in Hopedale, Labrador - Rollmann, Hans (Journal of Moravian history, 2020)
This exploration of literacy and awakening draws attention to the fact that the learning of hymns and the translation of the Passion narrative of the Gospels were instrumental in the acceptance of the Moravian faith among the Labrador Inuit. Literacy, made possible through systematic schooling since 1780, was thus an important factor in the awakening of 1804/5 in Hopedale and contributed to the indigenization of Christianity in the eighteenth-century Moravian settlements of Nain, Okak, and Hopedale. During the awakening a significant shift occurred in the religious self-understanding of the Labrador Inuit when people moved from a relatively superficial understanding of Christianity as a remedy for personal lapses and violations to an existential understanding of the drama of sin and salvation as well as a deeper identification with the religious community. The study also points out the fact that communication through written epistles between Labrador and Greenland may have established a wider religious bond of solidarity between Greenland and Labrador Inuit and encouraged the Hopedale Inuit during their awakening.